2013
DOI: 10.1165/rcmb.2012-0099oc
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide Nanoparticles Induce Matrix Metalloprotease 1 in Human Pulmonary Fibroblasts Partly via an Interleukin-1β–Dependent Mechanism

Abstract: Exposure to titanium dioxide (TiO2) nanoparticles (NPs) is associated with lung remodeling, but the underlying mechanisms are unknown. Matrix metalloprotease (MMP)-1 is an important actor in matrix homeostasis and could therefore participate in TiO2 NP effects. Our aim was to evaluate the effects of TiO2 NPs on MMP-1 expression and activity in lung pulmonary fibroblasts and to understand the underlying mechanisms and assess the importance of the physicochemical characteristics of the particles in these effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 65 publications
3
26
0
Order By: Relevance
“…Others have also shown that NLRP3 inflammasome activation by TiO 2 involves K + efflux but did not require NP uptake leading to neutrophil recruitment in vivo through IL-1 alpha secretion (Yazdi et al, 2010). The activation of the inflammasome could not only lead to inflammation but also to cell death through pyroptosis as observed for CB NPs (Reisetter et al, 2011) or induction of matrix metalloprotease 1 as shown for TiO 2 NPs in pulmonary fibroblasts (Armand et al, 2013). Recent studies have shown that in synergy with toll-like receptor ligands, certain CB NPs could promote the activation of the NLRP3 inflammasome.…”
Section: 3 Other Cellular Mechanisms Induced By Nanomaterialsmentioning
confidence: 95%
“…Others have also shown that NLRP3 inflammasome activation by TiO 2 involves K + efflux but did not require NP uptake leading to neutrophil recruitment in vivo through IL-1 alpha secretion (Yazdi et al, 2010). The activation of the inflammasome could not only lead to inflammation but also to cell death through pyroptosis as observed for CB NPs (Reisetter et al, 2011) or induction of matrix metalloprotease 1 as shown for TiO 2 NPs in pulmonary fibroblasts (Armand et al, 2013). Recent studies have shown that in synergy with toll-like receptor ligands, certain CB NPs could promote the activation of the NLRP3 inflammasome.…”
Section: 3 Other Cellular Mechanisms Induced By Nanomaterialsmentioning
confidence: 95%
“…Standards of MMP-9 (92 kDa) and MMP-2 (72 kDa) (Chemicon) were used to identify gelatinases. The enzymatic activity detected by casein zymography corresponding to MMP-1 was established based on its molecular mass of 54 kDa, being intensely expressed in pulmonary fibroblasts and MRC-5 cells [70,71].…”
Section: Gelatin and Casein Zymographymentioning
confidence: 99%
“…Perturbation of TGF-β1 signaling has been implicated in several developmental disorders and in various human diseases, including cancer, fibrosis and autoimmune diseases [35]. n-TiO 2 was found to be a potent inducer and regulator of matrix metalloproteinase-1 (MMP-1) and TGF-β expression and activity, partly via an IL-1β-dependent mechanism [36]. It has also been reported that the expression of TGF-β in mouse liver accelerates hepatocarcinogenesis and enhances DNA damage due to chronic oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, n-TiO 2 is a potent inducer of transforming growth factor-beta (TGF-β) expression, partly via an interleukin-1 beta (IL-1β)-dependent mechanism [5]. n-TiO 2 also induced higher levels of transcription factors, Smads, and growth factors [6].…”
Section: Introductionmentioning
confidence: 99%